RADIOLOGICAL INFORMATION SYSTEM: A NOVEL STUDY - RAHUL P KOTIAN,; NACHIKET GUDI,; BATULLA TEJASWARA REDDY, (International Journal of Pharma and Bio Sciences, 2016)
Background: Health is the fundamental right of every individual. Health care comprises of all the services provided to maintain the health of a person. Health care documentation also plays a vital role in assisting the providers to offer better care. Challenges faced in the management of electronic data in the health care industry are; capturing and sharing of patient data; especially the digital images have been an emerging challenge to the healthcare sector, language difference between HL7 and DICOM, the major problems faced by the use of broker software are; firstly its unidirectional workflow design and secondly paper based, leading to the duplication of data. Objective: The objectives of this study are to provide an understanding about RIS, information about the challenges faced by the healthcare industry during the introduction of the RIS, and establishing a comparison between the trends in the Western world and Asian countries. Methodology: Following the search a review of the related articles was carried out based on the content obtained. The review is a narrative literature review with focus on current trends, outcomes of integration of RIS to HIS and its advantage for all the stakeholders. Results: Based on the obtained articles the current trends were analysed with major emphasis laid on the outcomes of the integration of the RIS to the HIS and its effect on the overall hospital, patient and other stake holders benefits. Conclusion: The solutions to the challenges faced by the healthcare industry in the management of digital data is evident from the study, yet the question that provides scope for further study is the huge finance that is involved , its effective management and strategies to implement the integration on a large scale in developing countries.